Polysertularella polyseriata, a new genus and species of hydroid (Hydrozoa; Leptothecata; Sertulariidae) from the Sea of Okhotsk - Antsulevich, Alexander (Zootaxa, 2011)
Polysertularella polyseriata, gen. et sp. nov., a hydroid referable to family Sertulariidae, is described from the eastern part of the Sea of Okhotsk. The new taxa is characterized by: multi-serial (5–8 rows) placement of hydrothecae on both stem and branches; a hydrothecal rim with four small cusps; an operculum with four equal flaps similar to but more flattened than that of Sertularella. Gonothecae are transversely corrugated and resemble those of many species assigned to Sertularella and Symplectoscyphus. They arise from hydrothecae-like tubes on the basal part of the stem and are disposed in opposite pairs, as in species of Synthecium.Sertulariidae, the largest family in Hydrozoa and with representatives from marine environments worldwide, is relatively well known. Discovery of new genera in the family is relatively infrequent. A diagnosis of a new genus and a description of a new species are given in this paper.Diagnosis. Sertulariidae with erect, branched colonies, with branches resembling hydrocaulus. Hydrothecae arranged in 5–8 longitudal rows along hydrocaulus and branches; hydrothecal rim with four very low cusps separated by shallow embayments; operculum of four equal triangular valves, flattened rather than pyramidal; hydranth with abcauline caecum. Gonothecae oval with strong transverse corrugations and rings, occurring in opposite pairs on lower part of stem. Type species. Polysertularella polyseriata, sp. n., designated herein. Notes and differential diagnosis. In most genera of Sertulariidae, hydrothecae have an alternate to opposite biserial arrangement on branches, and especially on the stem. A few genera in the family, including Abietinaria Kirchenpauer, 1884, Thuiaria Fleming, 1828, Sertularia Linnaeus, 1758, and Staurotheca Allman, 1888 include some species with multi-serial rows of hydrothecae on branches and very rarely on the stem as well. The nominal genus Selaginopsis Allman, 1876, originally established for sertulariids having hydrothecae in more than two longitudinal rows, is no longer recognized as valid in some works because of its artificial composition and differences among included species in operculum structure (Peña-Cantero et al., 1997). However, no species with a multiserial arrangement of hydrothecae and four-flapped operculum (resembling Sertularella) has been known in the family until now.